Dilated Intercellular Spaces of Esophageal Epithelium among Malaysian With Nonerosive Reflux Disease: Transmission Electron Microscopic (Tem) Study - Myint, Yi Yi; Tun, Ye; Muhammad Amjad, Nasser; Mat Hassan, Mohd. Zailaini (2011)
Dilated intercellular space (DIS) is considered as early signs of acid damage to the esophageal epithelium. The diffusion of refluxed gastric acid into the intercellular space activates chemo sensitive nociceptors whose signals are transmitted via the spinal cord to the brain for symptom (heartburn) perception as well as initiated a short reflex arc to esophageal (longitudinal) smooth muscle as means of precipitating a sustained esophageal contraction.